Bacteriophage-Based Wound Care Formulation for Diabetic Ulcers as A Growth Inhibitor of Alcaligenes faecalis - Kiswara, Nur Hanifah Alim; Ludfillah, Rayyan Zhafir; Febrianti, Riska Ayu; Narulita, Erlia; Winarti, Lina (Al-Kauniyah: Jurnal Biologi, 2026)
Diabetic ulcers are frequently complicated by infections from multidrug-resistant bacteria such as Alcaligenes faecalis, necessitating the development of alternative therapeutic strategies. Bacteriophage therapy presents a promising approach due to its specificity and efficacy against antibiotic-resistant pathogens. This study aimed to formulate and evaluate a bacteriophage-based topical cleanser using the phage ϕAFaV1 for treating A. faecalis infections, focusing on high antibacterial efficacy and low dermal toxicity. Three suspension formulas (F1, F2, F3) were prepared with varying chitosan concentrations (0.5; 0.75, and 1.0%) as a suspending agent. These formulations underwent physical stability testing over 28 days, including assessments of viscosity, pH, zeta potential, and homogeneity. Antibacterial efficacy was determined through inhibition zone assays. All three formulations effectively inhibited bacterial growth, forming clear zones. The F2 formula (0.75% chitosan), containing 200 µL of active phage ingredient, was identified as the optimum formulation. It demonstrated superior physical stability and the most effective bactericidal activity against A. faecalis, as confirmed by statistical analysis. These results indicate that a bacteriophage suspension stabilized with 0.75% chitosan is a highly promising and stable topical agent for combating multidrug-resistant A. faecalis in diabetic wound care.